Pengembangan Booklet Learning How To Learn sebagai Layanan Informasi Mengenai Strategi Belajar Kognitif bagi Siswa SMA - Julistia Diah Nugraha; Sholih Sholih; Arga Satrio Prabowo (Ma'soem University, 2022)
This study aims to develop a learning how to learn booklet as an information service regarding cognitive learning strategies for high school students. The type of research used is research and development with research and development (R & D) Borg & Gall methods simplified by the Puslitjaknov Team (2008) which consists of conducting product analysis to be developed, developing initial products, expert validation and revision, trial small-scale field trials and revisions, large-scale field trials and final products. The sampling technique used was non-probability sampling by using quota sampling. The number of samples that will be involved in this study are 20 high school students (SMA) in Banten Province. This research is about product development in the form of a booklet that contains information on cognitive learning strategies that have aspects of 1) Repeating, 2) Elaborating, 3) Organization. To evaluate the product to be made, the researcher uses an evaluation model of alpha test and beta test. By asking material and media experts to assess the feasibility of the product as a way to evaluate, this is called an alpha test. The beta test is a form of product feasibility test based on the prospective user's assessment of the product being developed. After the product was tested for feasibility by material and media experts, then after being tested by students, whether the product developed was feasible or not, to get the results the researcher analyzed the data that had been obtained using the eligibility criteria according to Arikuntio (2009). In the product feasibility test, it was found that the results of the material expert test were 80%, the media expert test results were 87.05% and the user response test results were 84.26%. So from the results of the feasibility test and the respondent's trial, it was found that the product that the researcher developed in the form of a learning how to learn booklet was considered